Effects of High-Intensity Laser Therapy on Pain Sensitivity and Motor Performance in Patients with Thumb Carpometacarpal Joint Osteoarthritis: A Randomized Controlled Trial. - Cantero-Téllez, Raquel; Vilafañe, Jorge Hugo; Valdes, Kristin; García-Orza, Santiago; Bishop, Mark; Medina-Porqueres, Iván (My University, 2019)
Objective To examine the effects of high-intensity laser therapy (HILT) on pain sensitivity and motor performance in patients with thumb carpometacarpal (CMC) osteoarthritis (OA). Design Prospective, triple-blinded, randomized, placebo-controlled trial. Setting Private practice, Malaga, Spain. Subjects Forty-three patients (mean ± SD age = 71 ± 12 years) with a diagnosis of thumb CMC OA grade 1–2 were randomized to the control group (N = 21) or experimental group (N = 22). Methods The experimental group (ExpG) received high-intensity laser therapy (HILT), and the control group (ConG) received a placebo treatment. The outcome measures were pain intensity (visual analog scale) and key pinch strength measurements (dynamometer). All outcome measures were collected at baseline, immediately following the intervention, at four weeks, and at 12 weeks following the intervention. Results Analysis of variance revealed a group × time interaction (F = 40.8, P < 0.001) for pain intensity, with those patients receiving LT experiencing a greater reduction in pain compared with those receiving placebo therapy at the end of the intervention (P < 0.001), as well as at 12 weeks after the intervention. Although mean values in the ExpG were higher than in the ConG for key pinch at assessment, these differences were not statistically significant. Conclusions HILT effectively diminishes pain intensity when used as an isolated treatment for patients with thumb CMC OA, but the effect of treatment decreases after 12 weeks.
Keywords: Artrosis; Rayos láser - Uso terapéutico; Dolor - Aspectos fisiológicos; Pain; Thumb; Laser therapy; Osteoarthritis